UPAYA GERAKAN MILK TEA ALLIANCE DALAM MERESPON OTORITARIANISME DI INDONESIA DAN THAILAND - Martina Uliarta Siringoringo; M. Putra Prayoga; Yuni Amalia (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2025)
The phenomenon of democratic backsliding and the resurgence of authoritarianism has become a major concern in Southeast Asia, including in Indonesia and Thailand. This study aims to analyze how transnational civil society movements, particularly the Milk Tea Alliance (MTA), respond to and resist authoritarianism in these two countries. Using the theory of Transnational Advocacy Networks (TANs) by Keck and Sikkink, this study identifies the strategies of information politics, symbolic politics, leverage politics, and accountability politics employed by the MTA. The research adopts a qualitative-descriptive approach with literature study as the main method. The findings indicate that the MTA has succeeded in building cross-national solidarity that strengthens local advocacy, despite facing challenges such as state repression and nationalist resistance. These findings contribute to the understanding of the role of global civil networks in supporting democratization and civil liberties amidst the current wave of authoritarianism.